AWARENESS OF LYME BORRELIOSIS OF THE PATIENTS OF TERNOPIL REGIONAL TB DISPENSARY - Melnyk, L. P.; Hryshchuk, L. A.; Koziol–Montewka, M.; Tabas, P. S.; Klos, R. O. (International Journal of Medicine and Medical Research, 2017)
Background. Lyme disease has many clinical features similar tothose in sarcoidosis and tuberculosis. Epidemiological data in the world, in particular in Ukraine, proves the increase in Lyme borreliosis incidence. Ternopil region is endemic with Lyme borreliosis. Objective. The research was aimed to investigate the prevalence of infection with Borrelia burgdorferi and epidemiology features of borreliosis among the patients of Ternopil Regional TB Dispensary. Methods. In total, 29 patients were admitted to Departments of Differential Diagnostic, TB Therapy and TB Surgery of Ternopil Regional TB Dispensary in October 2016-January 2017. All the surveyed answered the questions of an integrated international questionnaire, where they noted the area and a number of tick bites, described the removal method, noted the survey for borreliosis pathogen and complaints after tick bites. Results. It was established that 5 respondents had a history of tick bites episodes, but only in one case the patient was examined of borreliosis. Tick bites were noticed in 3 patients with sarcoidosis and 1 with tuberculosis (TB) and exudative pleurisy, respectively. Conclusions. The absence of appeals for medical care, lack of sufficient information on Lyme borreliosis and disuse of preventive measures for tick bites by the interviewed patients of Ternopil regional TB dispensary departments proves the need of improvement of health education on Lyme borreliosis (LB) among this category of population. 24 (82.7%) of 29 respondents did not remember the tick bite. The symptoms of (LB) are similar to those in sarcoidosis and tuberculosis (pleural lesions, heart, joints, nervous system, skin), and the presence of tick bites gives the reasons to examine these patients of Borrelia burgdorferi senso lato.